Diplomatic protection and international arbitration under investment protection agreements between integration and competition (Damascus University Journal for legal sciences, 2022)
The protection of foreign investment enjoys an important place in international law because it represents an essential pillar in the achievement of the economic development of states. But with the rising prosperity of free movement of capital across continents, the investor needs a stronger and broader protection, free from the constraints of diplomatic protection, especially in the face of one of the investor's biggest concerns, namely disputes arising from investment with the host country, the result was the conclusion of several international agreements, that contributed to the development and recognition of the status of the foreign  investor.